Secular trends of birthweight in boys from 1950 to 2010 - Jimmy Célind; Marie Hedlund; Maria Bygdell; Arvid Sondén; Anders Elfvin; Jenny M. Kindblom (Elsevier, 2019)
Background: Birthweight is an indicator of fetal development and intrauterine conditions and is associated with future health outcomes. Secular birthweight trends prior to the 1970s are mostly unknown. Our aim was to explore secular birthweight trends in Swedish boys from 1950 to 2010. Methods: We have collected detailed growth data including birthweight from archived School Health Care records for children born in Gothenburg from 1946 and onwards and established a unique population-based cohort, the Body Mass Index Epidemiology Study (BEST). The birthweight cohort spans six decades (1950-2010) and includes 46,548 boys. Results: The mean birthweight of the complete study cohort was 3580 ± 562 g. Linear regression analysis of the entire period revealed a minimal negative secular trend for birthweight (BETA = −0.4 g/year; p < 0.01). However, three distinct trends appeared during sub-periods: a decrease 1950-80, an increase 1980-2000 and another decrease 2000-2010. Conclusion: We demonstrate that birthweight in boys has undergone periodic decreases and subsequent increases, but the overall trend from the 1950s to the present is stable. Key Words: birthweight, epidemiology, fetal growth, secular trends